Learning Painting Based on Ecological Wisdom: A Development Research to Enhance Visual-Spatial Intelligence of Universitas Negeri Medan Students - Muslim, Muslim; Diningrat, Raden Burhan Surya Nata; Akmal, Akmal (Gorga : Jurnal Seni Rupa, 2025)
This research is motivated by the lack of optimal learning activities and processes in developing students' spatial visual intelligence rationally and logically to create painting art in the UNIMED Fine Arts Education study program. This research aims to improve visual spatial intelligence and the quality of student paintings through the development of an ecology-based painting learning model. This development research uses the 4D model (defining, designing, developing, and disseminating). Based on the results of the study, it is known that; the design of the ecological wisdom-based painting learning model is based on an ecopedagogical learning approach. The design of this ecological wisdom-based painting learning model concretely adapts the syntax of the ELM Eco EA learning model and the free expression learning method. The adaptation of the ELM Eco EA learning model and free expression learning method is the basis for the design of the developed ecology-based painting learning model. The syntax and learning steps of these models and methods were reconstructed to produce a more contextualized hypothetical painting learning model design consisting of several steps, namely; 1) Preparation; 2) Providing Stimulus; 3) Investigation; 4) Determination of Theme; 5) Preparation of Tools and Materials; 6) Implementation; 7) Evaluation. After the developed learning model has met the eligibility criteria, overall the results of the data analysis of this trial are effective, this can be seen from the criteria for achieving classical completeness, achieving learning objectives, and student responses in accordance with the criteria specified in the learning and material studied.